Novel histone deacetylase 6 inhibitors using benzimidazole as caps for cancer treatment. (31st March 2023) - Nguyen, Phuong Hong; Hue, Bui Thi Buu; Pham, Minh Quan; Hoa, Tran Phuong; Tran, Quang De; Jung, Hosun; Hieu, Le Trong; Quoc, Nguyen Cuong; Quang, Hong Vinh; Quy, Nguyen Phu; Yoo, Hye Jin; Yang, Su-Geun
Abstract : A cap of benzimidazole and a four carbon-chain-containing thioether linker is a superior HDAC6 inhibitor to belinostat. Abstract : Histone deacetylases (HDACs) have proven to be promising targets for the development of anticancer drugs. In this work, we report the design and synthesis of a series of 19 novel hydroxamic acid-based histone deacetylase inhibitors conjugated to benzimidazole and benzoxazole core structures. Five compounds showed anti-proliferative activity with an IC50 value of 2.9–70.9 μM. Compound 7 displayed the highest efficacy against MCF-7 cells and exhibited antiproliferative effects against a panel of cancer cell lines. Compound 7 was the most potent selective inhibitor of HDAC6 and had an IC50 value 8- to >111.1-fold those of HDAC3, HDAC4, HDAC8, and HDAC11, and was a superior HDAC6 inhibitor to belinostat. Its interaction with and inhibitory activity on HDAC enzymes were then explored in a molecular docking study. The obtained data revealed the highest binding affinity (−8.46 kcal mol −1 ) of compound 7 toward HDAC6, as it formed interactions with the key residues Cys584 and Asp612 within the active site. Furthermore, the HDAC inhibitory activity of compound 7 was demonstrated from the dose-dependent increase in the tubulin acetylation level. Together, our results indicated that compound 7 with a cap of benzimidazole and four carbon-chain-containing thioether linker is a potent anticancer agent for selective HDAC6 inhibition and deserves further investigation.